2022
DOI: 10.3390/ijerph19074329
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Functional State of Cardiac Surgery Patients with Complicated Postoperative Period

Abstract: The purpose of this work was to study the factors determining the functional state of cardiac surgery patients with a complicated postoperative period upon discharge from the hospital. This observational study included 60 patients who underwent cardiac surgery with a complicated postoperative course and with a prolonged intensive care unit stay of more than 72 h. We assessed handgrip and lower-extremity muscle strength and the six-minute walk test (6MWT) distance 3 days after the surgery and at discharge from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…In our study, the median CBPT was 94 minutes. Similar to our results, in a recent observational study that included 60 patients who underwent cardiac surgery, Sumin et al demonstrated that CBPT was an independent predictor of functional state in patients with a complicated postoperative period upon discharge from the hospital 56 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the median CBPT was 94 minutes. Similar to our results, in a recent observational study that included 60 patients who underwent cardiac surgery, Sumin et al demonstrated that CBPT was an independent predictor of functional state in patients with a complicated postoperative period upon discharge from the hospital 56 .…”
Section: Discussionsupporting
confidence: 92%
“…There were no significant differences between the groups in postoperative outcomes (Table 4). The choice of the primary outcome of change in preoperative 6MWT from baseline was made after consultation with patients; reduced 6MWT is associated with moderate or severe complications after both noncardiac [15] and cardiac surgery [16]; conversely, improved 6MWT has been validated as an indicator of recovery in patients undergoing cardiac surgery [12,14,17]. Although a significant improvement in pre-operative exercise capacity was not observed in the prehabilitation cohort over standard care, it was observed in patients exhibiting sarcopenia measured by handgrip strength, which represented over a quarter of the trial population.…”
Section: Resultsmentioning
confidence: 99%
“…This study was conducted at the cardiovascular center, which is one of the largest CR centers in Japan [ 12 ], and phases I and II provide seamless CR. Phase II CR is based on established evidence, and in recent years, phase I CR has been advocated, including early postoperative mobilization and neuromuscular electrical stimulation, which is an important treatment strategy for improving short- and long-term prognoses [ 24 , 25 , 26 , 27 ]. Therefore, phase I and II CR are necessary to prevent hospital-acquired functional decline and MACE.…”
Section: Discussionmentioning
confidence: 99%